2010
DOI: 10.1002/pits.20473
|View full text |Cite
|
Sign up to set email alerts
|

The experience of bullying among secondary school students

Abstract: The present study was designed to qualitatively investigate secondary students' interpretations and experiences of bullying (and victimization) in Greek schools, with a focus on gender similarities and differences. Overall, 95 students (50 boys and 45 girls), 15 or 16 years old, participated in focus group interviews that were homogeneous in terms of grade and gender. Data analysis, using the interpretative phenomenological approach, showed that different interpretations and meanings of bullying between gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
1
30
0
4
Order By: Relevance
“…Additionally, victims often don't tell anyone that they are bullied, because they are not confident that others will take it seriously or they fear retaliation (Athanasiades & Deliyanni-Kouimtzis, 2010). Available Online at: http://grdspublishing.org/ Limitations of this study include its interest only in traditional bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, victims often don't tell anyone that they are bullied, because they are not confident that others will take it seriously or they fear retaliation (Athanasiades & Deliyanni-Kouimtzis, 2010). Available Online at: http://grdspublishing.org/ Limitations of this study include its interest only in traditional bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive relationships with teachers, classroom climate and teachers' attitude towards students, in addition to feeling safe and connected to the school, can provide pupils with the environmental and social support that is essential for mental health (Glover et al 2000;Pianta 2002). On the other hand, findings from a qualitative study by Athanasiades and Deliyanni-Kouimtzis (2010) have suggested that pupils do not perceive teachers as being supportive and portray them as indifferent toward bullying and ineffective in their interventions. Relationships with peers have also been found to play a critical role in the development of social skills and feelings that are necessary for personal growth and social adjustment (La Greca and Lopez 1998).…”
Section: Introductionmentioning
confidence: 91%
“…In dangerous situations, fear is an appropriate negative emotion relating to self-protection concerns (Blasi, 1999). Adolescents perceive bullying as a dangerous threat to their own safety and report fear as one of the main negative consequences of victimization (Athanasiades & Deliyanni-Kouimtzis, 2010). Fear of victimization deserves attention not only because it represents an emotional disturbance, but also because it may affect classroom concentration (Boulton et al, 2008) and school avoidance (Smith et al, 2004).…”
Section: Victimization and Fear Of Victimizationmentioning
confidence: 99%